Achilles tendon surgery in clubfoot: Are long term sequelae predictable? - Luisella Pedrotti; Barbara Bertani; Gabriella Tuvo; Redento Mora; Luca Marin; Federica De Rosa (PAGEPress Publications, 2022)
Congenital Clubfoot (CCF) treatment involves a surgical procedure on the Achilles tendon most of the time, i.e. tenotomy or, in selected cases, Z-plasty lengthening. Many authors have studied the outcomes of Achilles tenotomy, describing complete clinical and ultrasound tendon fibers integrity restoration 3-6 weeks after surgery. Nevertheless, little is known about the mechanical properties of the operated tendon. Recently, cases of subcutaneous rupture of the Achilles tendon have been described in adolescents who practiced sports and who had undergone Achilles tenotomy for congenital clubfoot in childhood. Authors report two cases of atraumatic Achilles tendon injury (subcutaneous rupture and intratendinous ossification) in adult patients who had been treated for congenital clubfoot in childhood. In both cases, no causes determining the injury were identified; in the medical history there was a Z-plasty lengthening of the Achilles tendon, performed within the first year of life, which could be considered a predisposing factor. The usefulness of long-term monitoring of patients treated for CCF with surgical procedures on the Achilles tendon is therefore hypothesized, in order to promptly identify by symptoms, clinical pictures and ultrasound criteria, tendon suffering that may predispose subcutaneous rupture.